Retroperitoneal vNOTES approach in early-stage endometrial cancer: a feasibility cohort with a contemporaneous laparoscopic comparison - Haliscelik, Mesut Ali; Oglak, Suleyman Cemil; Arkan, Kevser; Seker, Erdal; Bagli, Ihsan; Erkmen, Ali Deniz; Can, Behzat (Bmc, 2025)
Objective This study aimed to assess the feasibility, safety, and perioperative outcomes of the retroperitoneal vaginal natural orifice transluminal endoscopic surgery (vNOTES) approach for surgical staging in patients with early-stage endometrial cancer. A secondary objective was to compare perioperative and short-term results with those achieved using conventional laparoscopy performed by the same surgical team. Materials and methods Between June 2023 and June 2024, a retrospective study was conducted on 98 patients who underwent surgical staging for early-stage endometrial cancer. Patients were allocated to one of two groups: the vNOTES group (n = 49), who underwent retroperitoneal sentinel lymph node (SLN) biopsy, hysterectomy, and bilateral salpingo-oophorectomy (BSO); and the laparoscopic group (n = 49), who underwent the same procedures via a conventional laparoscopic approach. Demographic, surgical, and pathological parameters, as well as short-term follow-up outcomes, were compared between the two groups. Results The median operative time was significantly shorter in the vNOTES group than in the laparoscopic group (102 vs. 115 min, p < 0.001). SLN detection rates were identical between the groups (97.9% each). Postoperative pain scores on the Visual Analog Scale (VAS) were significantly lower in the vNOTES group at both 6 h (median 3 vs. 5) and 24 h (median 1 vs. 3) (p < 0.001 for both). Patients in the vNOTES group achieved earlier mobilization (median 5 vs. 6 h, p < 0.001) and had a shorter hospital stay (median 2 vs. 3 days, p < 0.001). The incidence of major complications did not differ significantly between the groups, and no recurrences were observed during a median follow-up period of 12 months. Conclusion The retroperitoneal vNOTES approach appears to be a feasible and safe technique for the surgical staging of early-stage endometrial cancer, providing perioperative benefits including shorter operative time, reduced postoperative pain, and faster recovery. The comparative findings with conventional laparoscopy should be interpreted as exploratory and require validation in larger prospective studies. Oncologic outcomes remain short-term and should be confirmed through long-term follow-up.
Keywords: Endometrial cancer; VNOTES; Laparoscopy; Sentinel lymph node; SLN; Minimally invasive surgery